Improving the stiffness of unidirectionally oriented weft-knitted structures for polymer matrix composite reinforcement - Araújo, Mário Duarte de (2009)
The use of weft-knitted structures in composite reinforcements is limited due to their poor mechanical properties. The tensile behaviour of weft-knitted fabrics is strongly restricted by its loop formation. When this type of structure is used as reinforcement, the mechanical properties of the composite material may be considerably hindered, as the resin may bear the initial load and fail before the load is transferred to the reinforcing fibres. However, weft-knitting is the most suitable technique for the production of 3D fabrics for complex shape composite reinforcements and so their stiffness must be improved. This paper reports on the progress that has been made to improving the modulus of elasticity of glass fibre fleece structures in the coursewise direction, in order to enable the production of tubular or flat preforms for composite materials with adequate stiffness.